On Sandwich Results of Meromorphic Multivalent Functions Defined by a New Hadamard Product Operator - Habeeb, Mohammed Abduljaleel; Atshan, Waggas Galib (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2023)
The goal of this research is to establish differential subordination and superordination findings for meromorphic multivalent functions defined by a new operator in a punctured open unit disk. We get a number of sandwich-type results.